Pengaruh Kecakapan Pribadi Dan Kecakapan Sosial Terhadap Keberhasilan Usaha Di Pusat Perbelanjaan Pasar Petisah Medan - Rachmahlija, Selfia; Lestari Nasution, Annio Indah; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The existence of small and Medium Enterprises (SMEs) in developing countries can be said to be the backbone of a country's economy. The success of small and medium enterprises (SMEs) has proven to be able to move the wheels of the nation's economy and reduce the number of unemployed in the country. In this study, researchers see the phenomenon that personal skills and social skills in business actors in the Petisah market is very minimal. In addition, there are also some efforts that look forward and crowded and some vice versa. This study aims to determine how the influence of personal skills and social skills on the success of businesses in the shopping center petisah medan market with respondents totaling 91 businesses selected through a simple random sampling technique. This study is an associative quantitative research. The variables of this study are personal skills and social skills and business success which consists of 7 dimensions, namely capital increase, production, number of customers, business expansion, expansion of marketing areas, improvement of physical facilities and business income. The research Data were analyzed using multiple linear regression analysis techniques and the results showed R^2 = 0.602 ; F = 66.521p_1= 0.573 p_2 = 0.932 the skills of business actors contributed 60.2% to the success of the business, personal skills and social skills have a positive and significant effect on business success. The results of this study are expected to provide an understanding of self-regulation and good communication skills and affect the success of the business so that business actors and prospective business actors can further develop it for the sake of a successful business undertaken.